Model-Model Gerakan NGO Lingkungan: Studi Kasus di Yogyakarta - Suharko, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1998)
This paper describes NGOs as an agent of environmental movement, especially in Yogyakarta. The paper focuses on modes of environmental movement. At least, there are three modes of environmental NG0s, that is: instrumental, sub-cultural, and contra-cultural movement. Environmental NGOs in Yogyakarta tend to have the same mode of one, although their activities varies. The mode of movement is sub-cultural movement. The NGOs movement does not change the dominant culture (capitalistic culture), which causes environmental poblems. Then- activities only encourage and support awareness and concern on environmental problems in the context of dominant culture.